2015
DOI: 10.2480/agrmet.d-15-00001
|View full text |Cite
|
Sign up to set email alerts
|

Possible soil frost control by snow compaction on winter wheat fields

Abstract: The appropriate control of soil frost depth could potentially balance wheat production and kill unharvested potato tubers. We examined possible soil frost control by snow compaction on winter wheat, without reducing wheat productivity. The target soil frost depth was more than 0.3 m, because our previous studies indicated the complete kill of unharvested potato tubers at such depths. The target frost depth was achieved by two snow compaction events following the development of a decision-making system by our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In terms of air temperatures in Japan, extremely low temperatures have sometimes been observed in northern regions during winter having thick and dry snowpack if the topographic and boundary layer conditions are suitable for strong cooling Kondo, 2000 . The winter air temperature affects the survival ratio and productivity of overwintering wheat e.g., Fowler et al, 1999;Shimoda et al, 2015 and fruit trees e.g., Ashworth and Wisniewski, 1991 . For example, the production of wine grapes has become widespread in Hokkaido during these decades Hirota et al, 2017 , and the winter air temperature determines suitable areas for wine grape cultivation to avoid frost damage Nemoto et al, 2016 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of air temperatures in Japan, extremely low temperatures have sometimes been observed in northern regions during winter having thick and dry snowpack if the topographic and boundary layer conditions are suitable for strong cooling Kondo, 2000 . The winter air temperature affects the survival ratio and productivity of overwintering wheat e.g., Fowler et al, 1999;Shimoda et al, 2015 and fruit trees e.g., Ashworth and Wisniewski, 1991 . For example, the production of wine grapes has become widespread in Hokkaido during these decades Hirota et al, 2017 , and the winter air temperature determines suitable areas for wine grape cultivation to avoid frost damage Nemoto et al, 2016 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested the use of a snowcompaction practice, called 'yuki-fumi' (Shimoda et al, 2015) to enhance the thermal conductivity of snowpack during cold periods. The differences in the timing and frequency of snow compaction can reduce the thermal insulation effect of snowpack, leading to lower soil temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Low winter temperatures and thin snowpacks are beneficial for the development of frost over soil depth profile. In previous studies, snow compaction was performed in the central part of the Tokachi region Shimoda et al, 2015). Even the southern part (STO) of the Tokachi region often experiences a large amount of snowfall during early winter due to the strengthening of low pressure along the southern coast (Hirota et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Low temperatures negatively impact structures and agricultural products, including orchards. On the other hand, agricultural techniques have been developed in cold and snowy regions to use low temperatures in applications such as soil frostcontrol weeding (Hirota et al 2011(Hirota et al , 2013Shimoda et al 2015;Yanai et al 2017;Yazaki et al 2013b;Shimoda and Hirota 2018) or buildings and storage-area cooling (Kimura et al 2010). These applications increase the need for accu rate winter agrometeorological forecasts, especially for air temperature.…”
Section: Introductionmentioning
confidence: 99%